NADPH-Thioredoxin Reductase C Mediates the Response to Oxidative Stress and Thermotolerance in the Cyanobacterium Anabaena sp. PCC7120 - Sánchez-Riego, Ana M.; Mata-Cabana, Alejandro; Galmozzi, Carla V.; Florencio, Francisco J. (Frontiers in Microbiology, 2016)
NTRC (NADPH-thioredoxin reductase C) is a bimodular enzyme composed of an NADPH-thioredoxin reductase and a thioredoxin domain extension in the same protein. In plants, NTRC has been described to be involved in the protection of the chloroplast against oxidative stress damage through reduction of the 2-Cys peroxiredoxin (2-Cys Prx) as well as through other functions related to redox enzyme regulation. In cyanobacteria, the Anabaena NTRC has been characterized in vitro, however nothing was known about its in vivo function. In order to study that, we have generated the first knockout mutant strain (∆ntrC), apart from the previously described in Arabidopsis. Detailed characterization of this strain reveals a differential sensitivity to oxidative stress treatments with respect to the wild-type Anabaena strain, including a higher level of ROS (reactive oxygen species) in normal growth conditions. In the mutant strain, different oxidative stress treatments such as hydrogen peroxide, methyl-viologen or high light irradiance provoke an increase in the expression of genes related to ROS detoxification, including AnNTRC and peroxiredoxin genes, with a concomitant increase in the amount of AnNTRC and 2-Cys Prx. Moreover, the role of AnNTRC in the antioxidant response is confirmed by the observation of a pronounced overoxidation of the 2-Cys Prx and a time-delay recovery of the reduced form of this protein upon oxidative stress treatments. Our results suggest the participation of this enzyme in the peroxide detoxification in Anabaena. In addition, we describe the role of Anabaena NTRC in thermotolerance, by the appearance of high molecular mass AnNTRC complexes, showing that the mutant strain is more sensitive to high temperature treatments.